2008
DOI: 10.1073/pnas.0804358105
|View full text |Cite
|
Sign up to set email alerts
|

IL-21 signaling is critical for the development of type I diabetes in the NOD mouse

Abstract: IL-21 is a pleiotropic type I cytokine that shares the common cytokine receptor ␥ chain and plays important roles for normal Ig production, terminal B cell differentiation to plasma cells, and Th17 differentiation. IL-21 is elevated in several autoimmune diseases, and blocking its action has attenuated disease in MRL/lpr mice and in collagen-induced arthritis. The diabetes-associated Idd3 locus is at the Il2/Il21 locus, and elevated IL-21 was observed in the nonobese diabetic (NOD) mouse and suggested to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
161
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(170 citation statements)
references
References 28 publications
6
161
3
Order By: Relevance
“…IL-21 is necessary for the development of diabetes in the NOD mouse (23)(24)(25), but a number of important studies argue that decreased expression of IL-2 explains Idd3 (14,15,31). Our findings resonate with a critical role for IL-21 in T1D pathogenesis, but do not formally discount a role for IL-2.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…IL-21 is necessary for the development of diabetes in the NOD mouse (23)(24)(25), but a number of important studies argue that decreased expression of IL-2 explains Idd3 (14,15,31). Our findings resonate with a critical role for IL-21 in T1D pathogenesis, but do not formally discount a role for IL-2.…”
Section: Discussioncontrasting
confidence: 56%
“…IL-21 is produced by activated CD4 ϩ T cells and NK T cells, and can deliver a costimulatory signal to lymphocytes that affects their proliferation, differentiation, and survival in response to antigen (19)(20)(21). Consistent with its actions on lymphocyte populations, IL-21 has been shown to have an essential role in an array of conditions involving the destruction of self-tissues (20,(22)(23)(24). We have previously shown that NOD mice exhibited elevated levels of IL-21 (26), and a number of recent studies of NOD mice made genetically deficient in the IL-21R demonstrate that IL-21 is necessary for the development of T1D (23)(24)(25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also critical for B-cell differentiation into plasma cells and Ig production (9,10) and negatively regulates the function of dendritic cells (11). IL-21 plays a role in autoimmune diseases, including type I diabetes in nonobese diabetic mice (12,13), systemic lupus erythematosus in MRL/lpr and BXSB/Yaa mice (9,14,15), and collagen-induced arthritis (16). In experimental allergic encephalitis (EAE), divergent effects of IL-21 have been reported related to its role in the development and progression of the autoimmune response as well as whether it is required for disease development (1,17,18).…”
mentioning
confidence: 99%
“…Coevolution of the IL-21 and IL-2 systems is further suggested not only by their sharing of γ c but also by the fact that IL-21R is most closely related to IL-2Rβ (20); nevertheless, IL-21 and IL-2 have distinct functions. For example, IL-21 is implicated in the development of autoimmunity (9,(12)(13)(14)16), but mice deficient in IL-2, IL-2Rα, and IL-2Rβ exhibit autoimmunity (21)(22)(23)(24), suggesting that IL-2 protects against development of autoimmune disease. IL-21 can promote the development of Th17 cells, whereas IL-2 inhibits the differentiation of Th17 cells (25), although it induces the expansion of Th17 cells that mediate uveitis and scleritis (26).…”
mentioning
confidence: 99%